Mémoire : the sound of home - Kwah, Hannah En Hui (2019)
Mémoire uses both furniture and recorded conversations with my family in the medium of mixed media installation to explore the space of a living room. The installation is meant to reflect the interactions I have with my family in this intimate space, to relive past experiences associated with this space, and to help people ponder deeper over the meaning of a space that is at once comfortable and vulnerable.